(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The reading book of elementary adjectives did not even provide information about expressions when we observed native language books. But the fact that phrases are given in the texts of most of the primary school textbooks indicates that the topic of phrases is relevant in the primary grades. In particular, in the elementary school textbook, expressions are used in many texts. This requires the teacher to inform the students about the expressions.